The Effect of Learning Capabilities and Technical Competencies on the Performance of Non-Organic Employees in Bank Indonesia Representative Offices, Central Java Province - M. Solikan; Hendar (Majapahit Journal of Islamic Finance and Management, 2026)
This study was proposed to describe and analyze the influence of learning capabilities on the performance of non-organic employees in KpwBI Prov. Central Java, describes and analyzes the influence of learning capabilities on the competence of non-organic employees in KpwBI Prov.Central Java, describes and analyzes the influence of competence on the performance of non-organic employees in KpwBI Prov.Central Java. This research is quantitative with an explanatory research approach.  The main objective is to test the causal relationship between independent variables (learning capabilities) and bound variables (HR performance) with Competency as a mediating variable. The quantitative approach was chosen because the research demands hypothesis testing and estimation of the parameters of the relationship between variables statistically. The primary collection method is a cross-sectional survey using a structured questionnaire. For causal and mediation analysis, Structural Equation Modeling (SEM) was used. The population in this study is non-organic employees at the Bank Indonesia representative office in Central Java Province. The sample in this study was 125 non-organic employees. Data analysis using the Partial Least Square (PLS) method with SmartPLS. The results of the study show that learning capabilities are proven to have a positive and significant influence on employee technical competence, learning capabilities also have a positive effect on employee performance, technical competence is proven to have a significant positive effect on employee performance.